Investigation of growing the Hg₁₋x₋y₋zAxByCzTe solid solutions by modified zone melting method - Gorbatyuk, I.N.; Zhikharevich, V.V.; Ostapov, S.E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
This paper presents research of the process for growing the crystals of semiconductor solid solutions Hg₁₋x₋y₋zAxByCzTe under conditions of a modified zone melting.